2006
DOI: 10.1248/bpb.29.1645
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Mutagenesis of the Serotonin 5-Hydroxytryptamine2C Receptor: Identification of Amino Acids Responsible for Sarpogrelate Binding

Abstract: Site-directed mutagenesis was used to investigate the molecular interactions involved in sarpogrelate binding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…K D values derived from saturation binding isotherms of [ 3 H]-mesulergine labeled WT, S3.36A and Y7.43A 5-HT 2C receptors. No specific binding of [ 3 H]-mesulergine to the D3.32A point-mutated 5-HT 2C receptor was detected (not shown), consistent with results previously reported (Muntasir et al, 2006). Affinity of [ 3 H]-mesulergine at the WT, S3.36A and Y7.43A point-mutated receptors was not significantly different (mean (S.E.M.)…”
Section: Resultssupporting
confidence: 92%
“…K D values derived from saturation binding isotherms of [ 3 H]-mesulergine labeled WT, S3.36A and Y7.43A 5-HT 2C receptors. No specific binding of [ 3 H]-mesulergine to the D3.32A point-mutated 5-HT 2C receptor was detected (not shown), consistent with results previously reported (Muntasir et al, 2006). Affinity of [ 3 H]-mesulergine at the WT, S3.36A and Y7.43A point-mutated receptors was not significantly different (mean (S.E.M.)…”
Section: Resultssupporting
confidence: 92%
“…Recently, similar results for α 1b -AR were obtained in our laboratory (27). Mutation of the same conserved aspartate residue on 5-HT 2C and 5-HT 2B also showed no ligand binding or 5-HT stimulated IP formation in our laboratory (28,29). These results may be extrapolated to the conserved aspartate at position 176 in α 1d -AR.…”
Section: Agonist-stimulated Ip Accumulationsupporting
confidence: 87%
“…With the help of molecular modeling and mutagenesis studies of 5-HT 2B receptors, we previously identified the important binding sites of sarpogrelate to 5-HT 2A -and 5-HT 2C receptors (6,7). Molecular modeling of sarpogrelate to the 5-HT 2B receptor predicted that sarpogrelate makes strong electrostatic interactions towards aspartic acid (Asp) 135 in transmembrane helix (TMH) 3 of the 5-HT 2B receptor (8).…”
mentioning
confidence: 99%